Recent Advances in the Therapeutic and Diagnostic Use of Liposomes and Carbon Nanomaterials in Ischemic Stroke - Fernandes, Lorena F.; Bruch, Gisele E.; Massensini, André R.; Frézard, Frédéric (Frontiers in Neuroscience, 2018)
The complexity of the central nervous system (CNS), its limited self-repairing capacity and the ineffective delivery of most CNS drugs to the brain contribute to the irreversible and progressive nature of many neurological diseases and also the severity of the outcome. Therefore, neurological disorders belong to the group of pathologies with the greatest need of new technologies for diagnostics and therapeutics. In this scenario, nanotechnology has emerged with innovative and promising biomaterials and tools. This review focuses on ischemic stroke, being one of the major causes of death and serious long-term disabilities worldwide, and the recent advances in the study of liposomes and carbon nanomaterials for therapeutic and diagnostic purposes. Ischemic stroke occurs when blood flow to the brain is insufficient to meet metabolic demand, leading to a cascade of physiopathological events in the CNS including local blood brain barrier (BBB) disruption. However, to date, the only treatment approved by the FDA for this pathology is based on the potentially toxic tissue plasminogen activator. The techniques currently available for diagnosis of stroke also lack sensitivity. Liposomes and carbon nanomaterials were selected for comparison in this review, because of their very distinct characteristics and ranges of applications. Liposomes represent a biomimetic system, with composition, structural organization and properties very similar to biological membranes. On the other hand, carbon nanomaterials, which are not naturally encountered in the human body, exhibit new modes of interaction with biological molecules and systems, resulting in unique pharmacological properties. In the last years, several neuroprotective agents have been evaluated under the encapsulated form in liposomes, in experimental models of stroke. Effective drug delivery to the brain and neuroprotection were achieved using stealth liposomes bearing targeting ligands onto their surface for brain endothelial cells and ischemic tissues receptors. Carbon nanomaterials including nanotubes, fullerenes and graphene, started to be investigated and potential applications for therapy, biosensing and imaging have been identified based on their antioxidant action, their intrinsic photoluminescence, their ability to cross the BBB, transitorily decrease the BBB paracellular tightness, carry oligonucleotides and cells and induce cell differentiation. The potential future developments in the field are finally discussed.